Our century 1920-1930 - Napoli, Tony (Milwaukee Gareth Stevens Publishing, 1993)
This "magazine" style history series reinforces the reality of history and makes reading about it more engaging to the student. Topics include daily life, around the world, back at home, sports world, arts, people in the news, and more.
Includes bibliographical references and index
6 - 12 years
Keywords: History, Modern -- Juvenile Literature -- 20th century